Estradiol enables chronic corticosterone to inhibit pulsatile LH secretion and suppress Kiss1 neuronal activation in female mice - Kreisman, Michael J. (Neuroendocrinology, 2019)
INTRODUCTION: Two common responses to stress include elevated circulating glucocorticoids and impaired luteinizing hormone (LH) secretion. We have previously shown that a chronic, stress-level of corticosterone can impair ovarian cyclicity in intact mice by preventing follicular-phase endocrine events. OBJECTIVE: Here, we sought to investigate if corticosterone can disrupt LH pulses and whether estradiol is necessary for this inhibition. METHODS: Our approach was to measure LH pulses prior to and following administration of chronic corticosterone or cholesterol in ovariectomized mice treated with or without estradiol, as well as assess changes in arcuate kisspeptin (Kiss1) neuronal activation, as determined by co-expression with c-Fos. RESULTS: In ovariectomized mice, a chronic 48h elevation in corticosterone did not alter the pulsatile pattern of LH. In contrast, corticosterone induced a robust suppression of pulsatile LH secretion in mice treated with estradiol. This suppression represented a decrease in pulse frequency without a change in amplitude. We show that the majority of arcuate Kiss1 neurons contain glucocorticoid receptor, revealing a potential site of corticosterone action. Although arcuate Kiss1 and Tac2 gene expression did not change in response to corticosterone, arcuate Kiss1 neuronal activation was significantly reduced by chronic corticosterone, but only in mice treated with estradiol. CONCLUSIONS: Collectively, these data demonstrate that chronic corticosterone inhibits LH pulse frequency and reduces Kiss1 neuronal activation in female mice, both in an estradiol-dependent manner. Our findings support the possibility that enhanced sensitivity to glucocorticoids, due to ovarian steroid milieu, may contribute to reproductive impairment associated with stress or pathophysiologic conditions of elevated glucocorticoids.